2015
DOI: 10.1007/s10753-015-0183-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Saline (NaCl 7.5 %) Reduces LPS-Induced Acute Lung Injury in Rats

Abstract: Acute respiratory distress syndrome (ARDS) is the most severe lung inflammatory manifestation and has no effective therapy nowadays. Sepsis is one of the main illnesses among ARDS causes. The use of fluid resuscitation is an important treatment for sepsis, but positive fluid balance may induce pulmonary injury. As an alternative, fluid resuscitation with hypertonic saline ((HS) NaCl 7.5%) has been described as a promising therapeutical agent in sepsis-induced ARDS by the diminished amount of fluid necessary. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…There have been concerns around the association of hypernatraemia and mortality in unselected cohort of patients . However, based on our results, previous animal studies and provided that the hypernatraemia is induced safely (i.e. shift of <12 mmol in 24 h), we anticipate that there will be protective effect of hypernatraemia in patients with acute lung injury.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…There have been concerns around the association of hypernatraemia and mortality in unselected cohort of patients . However, based on our results, previous animal studies and provided that the hypernatraemia is induced safely (i.e. shift of <12 mmol in 24 h), we anticipate that there will be protective effect of hypernatraemia in patients with acute lung injury.…”
Section: Discussionmentioning
confidence: 72%
“…Similar to hyperosmolarity, induced hypernatraemia has also been shown to be protective in acute lung injury, with proposed mechanisms being a decrease in cellular infiltrate 8 and preservation of alveolar surfactant. 9 In keeping with this evidence, we observed previously that the phenomenon of increased ICU mortality with hypernatraemia in an unselected cohort of patients does not occur in patients with a pulmonary diagnoses, particularly those with PaO 2 /FiO 2 ratios <200.…”
Section: Summary At a Glancementioning
confidence: 99%
“…A role of chloride in the activation of the NLRP3 inflammasome has also been indicated from the inhibitory effect of high extracellular NaCl, and the chloride inhibitors NPPB and DIDs [23,24,44]. In addition, the use hypertonic solutions has been widely used to the treatment of acute conditions, such as ischemic stroke, and intracerebral hemorrhage [45,46], and has also shown to have beneficial effects in the treatment of patients with septic shock [47][48][49]. Contrary to this studies, Ip et al, reported high extracellular osmolarity being pro-inflammatory [38].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertonic saline has shown benefits in animal studies, studies reported significantly lower lung injury and oedema associated with hypertonic saline administration, which is also associated with lower rate of mortality 166-167 . TNF-α inhibition has shown promising results in animal model of ALI, which may warrant further human studies with existing anti-TNF therapy 168-169 .…”
Section: Conclusion and Way Forwardmentioning
confidence: 99%